2022 17th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2022
DOI: 10.1109/hri53351.2022.9889468
|View full text |Cite
|
Sign up to set email alerts
|

Gender Fairness in Social Robotics: Exploring a Future Care of Peripartum Depression

Abstract: In this paper we investigate the possibility of socially assistive robots (SARs) supporting diagnostic screening for peripartum depression (PPD) within the next five years. Through a HRI/socio-legal collaboration, we explore the gender norms within PPD in Sweden, to inform a gender-sensitive approach to designing SARs in such a setting, as well as governance implications. This is achieved through conducting expert interviews and qualitatively analysing the data. Based on the results, we conclude that a gender-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Specifically developers of social robots have been scrutinised by Richardson [25] through observing developers creating social robots at MIT; Strengers and Kennedy [26] mapping out the discourse behind social robots and its significance; and Šabanović [27] a social roboticist showcasing how developers in Japan have to follow conservative values so that the robot will be accepted within everyday society. Tanqueray et al [28] represent a collaboration between SoL and HRI scholars. This collaboration enabled to outline norms within the context of peripartum depression, and how this can be incorporated into the design of social robots to screen for peripartum depression [28].…”
Section: Social Structures and Normsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically developers of social robots have been scrutinised by Richardson [25] through observing developers creating social robots at MIT; Strengers and Kennedy [26] mapping out the discourse behind social robots and its significance; and Šabanović [27] a social roboticist showcasing how developers in Japan have to follow conservative values so that the robot will be accepted within everyday society. Tanqueray et al [28] represent a collaboration between SoL and HRI scholars. This collaboration enabled to outline norms within the context of peripartum depression, and how this can be incorporated into the design of social robots to screen for peripartum depression [28].…”
Section: Social Structures and Normsmentioning
confidence: 99%
“…Tanqueray et al [28] represent a collaboration between SoL and HRI scholars. This collaboration enabled to outline norms within the context of peripartum depression, and how this can be incorporated into the design of social robots to screen for peripartum depression [28].…”
Section: Social Structures and Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our scenario is grounded in previous studies exploring PND prediction through mobile phone data (Zhong et al, 2022), and social robotics in PND (Zhong et al, 2021;Tanqueray et al, 2022). Ultimately, the purpose of the robot is to encourage those predicted to be most at risk of PND to accept a follow-up appointment with a specialist clinician.…”
Section: Scenariomentioning
confidence: 99%
“…Work on conversational agents has demonstrated that gender bias and expectations of behaviour map into humanmachine interactions, even in the context of unimodal speechbased interactions [42,43]. Such work, in part, motivated UNESCO critique of gendered AI in the context of the continuing digital skills divide [4], which in turn has motivated work examining gender-norm breaking robot behaviour and applications in HRI [6,44].…”
Section: Gender Stereotypesmentioning
confidence: 99%